(untitled) (International Journal of Physiotherapy, 2017)
Background: Poor posture is detrimental to breathing. Our purpose was to investigate the effect of upright and hunchbacked sitting on thoracic configuration and changes in the volume of the thorax during quiet and volitional deep breathing. Methods: The participants were 11 healthy men with a mean age of 21.6 years, mean body mass of 59.8 kg, mean height of 169.7 cm and a body mass index of 20.7 kg/m2. Eighty-four reflective markers were placed on the trunk. Three-dimensional motion analysis measured the volume within the hemithoraces. To calculate upper and lower thoracic volumes, six imaginary hexahedra were visualized using four reflective markers for each on both aspects of the thorax. Each hexahedron was divided into three imaginary triangular pyramids to calculate positional vectors. Finally, the volume for the hexahedra and triangular pyramids was calculated. Upper thoracic volume encompassed a space from the sternal notch to a midpoint on the ventral aspect of the third rib and the lower thoracic volume from the xiphoid process to the midpoint on tenth rib’s dorsal aspect. Results: In hunchbacked sitting during quiet breathing the left lower hemithorax yielded a significantly larger volume (p=0.003), and both breathing patterns during inspiration and expiration yielded a significantly greater change in thoracic configuration (p=0.01, p=0.016). Conclusion: Findings suggested that, in a hunchbacked sitting, there was decreased thoracic asymmetry with re-establishment of thoracic vertebral alignment, consequently stabilizing the sitting position, but breathing was suppressed and tidal volume decreased. Physiotherapy should aim at ensuring correction of hunchbacked posture and maintenance of thoracic symmetry.